EFFECTS OF BICYCLE HELMET LAWS ON CHILDREN'S INJURIES. (30th September 2013) - Markowitz, Sara; Chatterji, Pinka
ABSTRACT: In recent years, many states and localities in the USA have enacted bicycle helmet laws. We estimate the effects of these laws on injuries requiring emergency department treatment. Using hospital‐level panel data and triple difference models, we find helmet laws are associated with reductions in bicycle‐related head injuries among children. However, laws also are associated with decreases in non‐head cycling injuries, as well as increases in head injuries from other wheeled sports. Thus, the observed reduction in bicycle‐related head injuries may be due to reductions in bicycle riding induced by the laws. Copyright © 2013 John Wiley & Sons, Ltd.